The Addams family [videorecording (DVD)] - Sonnenfeld, Barry; Huston, Anjelica; Julia, Raul; Lloyd, Christopher, 1938-; Addams, Charles, 1912-1988 (Warner Home Video, 2013)
Long-lost Uncle Fester reappears in the lives of the ghoulish Addams family, headed by Morticia and Gomez.